The end of destitution - Ian Gazeley; Andrew Newell (Institute for the Study of Labor (IZA), 2009)
The paper presents a statistical generalisation, to working families in the whole of Britain, of Rowntree's finding that absolute poverty declined dramatically in York between 1899 and 1936. We use poverty lines devised by contemporary social investigators and two relatively newly-discovered data sets. We estimate an almost complete elimination of absolute poverty among working households for the whole of the Britain between 1904 and 1937. We offer a number of pieces of corroborative evidence that give support to our findings. We decompose the poverty reduction into the effects of two proximate causes, of roughly equal importance, the decline in family size and the rise of real wages. We conclude with some speculation about the deeper causes of the decline.
urn:nbn:de:101:1-20090824230
Keywords: N3; O12; 330; Poverty; living standards; Britain; demographic change; real wage growth; Armut; Lebensstandard; Reallohn; Wirtschaftsgeschichte; Demographischer Übergang; Familiensoziologie; Großbritannien